New Insights Into Implications of CTRP3 in Obesity, Metabolic Dysfunction, and Cardiovascular Diseases: Potential of Therapeutic Interventions - Guo, Bei; Zhuang, Tongtian; Xu, Feng; Lin, Xiao; Li, Fuxingzi; Shan, Su-Kang; Wu, Feng; Zhong, Jia-Yu; Wang, Yi; Zheng, Ming-Hui; Xu, Qiu-Shuang; Ehsan, Ullah Muhammad Hasnain; et al. (Frontiers in Physiology, 2020)
Adipose tissue, as the largest endocrine organ, secretes many biologically active molecules circulating in the bloodstream, collectively termed adipocytokines, which not only regulate the metabolism but also play a role in pathophysiological processes. C1q tumor necrosis factor (TNF)-related protein 3 (CTRP3) is a member of C1q tumor necrosis factor-related proteins (CTRPs), which is a paralog of adiponectin. CTRP3 has a wide range of effects on glucose/lipid metabolism, inflammation, and contributes to cardiovascular protection. In this review, we comprehensively discussed the latest research on CTRP3 in obesity, diabetes, metabolic syndrome, and cardiovascular diseases.